Craniofacial and upper airway morphological characteristics associated with the presence and severity of obstructive sleep apnea in Chinese children - Qiuping Xu; Qiuping Xu; Qiuping Xu; Xiaoya Wang; Xiaoya Wang; Xiaoya Wang; Na Li; Ying Wang; Xin Xu; Jing Guo; Jing Guo (Frontiers Media S.A., 2023)
ObjectivesTo identify craniofacial and upper airway morphological characteristics associated with the presence and severity of obstructive sleep apnea (OSA) in children.MethodsThis study consisted of 82 OSA children and 77 controls (age 5-10 years). All subjects underwent cephalograms and were divided into a 5-7 age group and an 8-10 age group. Cephalometric variables were compared between OSA children and controls, and hierarchical regression analysis was performed to examine the relationship between cephalometric variables and OSA severity [expressed by the obstructive apnea-hypopnea index (OAHI)] in different age groups.ResultsIncreased A/N ratio, narrowed posterior airway space, decreased SNA and SNB angles, and shortened ramus height were observed among OSA children in different age groups. In the 5-7 age group, the A/N ratio and a lower gonial angle explained 40.0% and 14.7% of the variance in the OAHI, respectively. In the 8-10 age group, the BMI z-score and A/N ratio explained 25.2% and 6.6% of the variance in the OAHI, followed by a lower gonial angle and the hyoid-retrognathion distance (19.1% in total).ConclusionsAdenoid hypertrophy was a major factor associated with OSA in preschool children, whereas obesity replaced adenoid hypertrophy as the main contributor to OSA in late childhood. Several craniofacial skeletal variables such as the SNB angle, ramus height, lower gonial angle, and hyoid position are also associated with the presence and/or severity of OSA, which could be used to help recognize children at a higher risk for OSA.